Implementation of Enhanced Milieu Teaching Intervention on the Communication of Children with Autism - Rachmasari, Finy; Wulandari, Primatia Yogi (Psikoborneo: Jurnal Ilmiah Psikologi, 2024)
Communication is a crucial skill for every individual and needs to be developed from a young age. Communication facilitates learning and sharing of knowledge and experiences among individuals. For children, communication skills play a significant role in shaping their future behaviors and attitudes. Especially for children with autism, the ability to communicate is essential for fostering independence and participation in daily activities. This research aims to assist in developing communication skills in children with autism by enhancing various language aspects. The subject of this study is a four-year-old boy diagnosed with autism. The research adopts a single-case experimental design with an A-B-A structure, consisting of baseline 1, intervention, and baseline 2 phases. The intervention applied in this study is Enhanced Milieu Teaching (EMT). The research process began with establishing baseline 1 through data collection methods such as interviews, the administration of the VSMS psychological test, and observations (narrative observations in daily life and language milestones). Subsequently, the EMT intervention was implemented over nine sessions, with each session comprising two EMT treatment procedures. Following the completion of the intervention, baseline 2 was established through daily life observations of the subject during communication. The research results indicate an improvement in communication skills in children with autism through the Enhanced Milieu Teaching (EMT) intervention.Komunikasi merupakan kemampuan yang penting dimiliki oleh setiap individu dan perlu dikembangkan sejak usia kanak-kanak. Hal ini mengingat melalui komunikasi akan membantu antar individu saling belajar dan berbagi pengetahuan serta pengalaman, terutama bagi anak kemampuan komunikasi ini menjadi aspek yang penting mengingat kemampuan komunikasi sebagai salah satu faktor yang mempengaruhi pembentukan sifat dan sikap anak di masa mendatang. Demikian juga pada anak dengan autisme, kemampuan komunikasi juga menjadi hal yang penting untuk dikembangkan karena akan membantu mempengaruhi kemandirian anak untuk berpartisipasi dalam kegiatan sehari-hari. Penelitian ini bertujuan untuk membantu mengembangkan kemampuan komunikasi pada anak autisme dengan meningkatkan aspek-aspek berbahasa. Subjek pada penelitian ini adalah seorang anak laki-laki berusia empat tahun yang terdiagnosa mengalami autisme. Jenis penelitian ini menggunakan single case experimental dengan desain A-B-A yang terdiri dari baseline 1, intervensi, dan baseline 2. Intervensi yang diterapkan pada subjek adalah enhanced milieu teaching (EMT). Intervensi diawali dengan menggali baseline 1 melalui pengumpulan data menggunakan wawancara, administrasi tes psikologi VSMS, serta observasi (naratif di keseharian dan milestone bahasa). Kemudian diterapkan intervensi enhanced milieu teaching (EMT) selama sembilan sesi dengan setiap sesi terdiri atas dua kali perlakuan prosedur EMT. Setelah intervensi selesai diberikan dilakukan penggalian baseline 2 melalui observasi keseharian subjek selama berkomunikasi. Hasil penelitian menunjukkan adanya peningkatan kemampuan komunikasi pada anak dengan autisme melalui intervensi enhanced milieu teaching (EMT).